O Movimento Do Pensamento Teórico De Professores Sobre O Conceito De Fração E O Sentido Atribuído Aos Materiais Didáticos Na Atividade De Ensino - Romeiro, Iraji De Oliveira [UNIFESP] (2017)
The present research investigated how the development of the theoretical thinking of teachers of mathematics in teaching activity on the concept of fraction impacts on the choice, use and adequacy of didactic materials, in particular, the materials that make up the Official Curriculum of the State of São Paulo. The theoretical references adopted involve the historical-cultural perspective, the Theory of Activity and the Theory of Developmental Teaching. From this perspective, didactic materials are understood as instruments mediating the practice and organization of teaching by teachers. In order for the development of theoretical thought to be observed, we adopted the dialectical historical materialism as a method of investigation through a formative experiment that was objectified in a continuous formation course for a singular group of mathematical teachers. In order for teachers to understand the concept of a fraction in its genesis, it was proposed the learning-triggering situations, based on the concept of Teaching Guidance Activity, so that teachers in the community could come across the logicalhistorical context of fractions and with this appropriation of elements of the theoretical knowledge of the concept. For the analysis of the data we used the concept of isolated and organized in two of them: "Movement of theoretical thinking about fractions" and "Didactic material as mediator of teacher action". These two isolates are dialectically related in this research and are systematized by episodes. In the analysis of the data, from the speeches and actions of the teachers in the formative experiment, we sought to evidence the movement of development of theoretical thinking and overcoming of empirical thought in search of a theoretical conception and how this overcoming impacted on the meanings attributed to mediating instruments. The results of the research point out that from the development of theoretical thinking teachers seek the best mediating instruments to materialize their objective in teaching activity. In particular, in developing the theoretical thinking about the concept of fraction, they attributed to the official didactic material that composes the Official Curriculum of the State of São Paulo a new meaning, recognizing it as a mediator in the organization of education that demands the search for other instruments Involving all elements that favor the development of theoretical thinking about fractions. In this sense, the official didactic material came to be at the service of the teacher as mediator of his teaching activity and not the opposite. Thus, the development of theoretical thinking, the conscious and intentional organization of teaching and the choice of mediating instruments that serve the teaching activity, distances the teacher from a professional who only performs public policies, characterizing him as a more autonomous and creative professional.